2015
DOI: 10.1039/c5ja00354g
|View full text |Cite
|
Sign up to set email alerts
|

Regionalized quantitative LA-ICP-MS imaging of the biodegradation of magnesium alloys in bone tissue

Abstract: LA-ICP-MS data were spatially referenced to the respective microscope images to investigate the biodegradation of Mg alloys in bone tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…With advances in Mg alloy research, many authors have suggested the importance of the quantitative determination of the spatial Mg accumulation for understanding the degradation process and the interaction between Mg release and biological responses [ 9 ]. However, no studies were focused on intervertebral Mg accumulation as most of the previous studies were performed for Mg-based screws [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…With advances in Mg alloy research, many authors have suggested the importance of the quantitative determination of the spatial Mg accumulation for understanding the degradation process and the interaction between Mg release and biological responses [ 9 ]. However, no studies were focused on intervertebral Mg accumulation as most of the previous studies were performed for Mg-based screws [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LA ICP-QMS measurements to detect the spatial distribution of 138 Ba/ 43 Ca ratios of the thin sections of the i2s from ind1, ind2 and ind3 were performed using a nanosecond excimer-based laser ablation system (NWR 193, ESI-NWR Division, Electro Scientific Industries, Inc., Portland, CA, USA) coupled to an ICP-QMS (NexION 350D, Perkin Elmer, Waltham, MA, USA) similar to the protocol of Draxler et al 90 . Further multi-elemental distributions were monitored to define the tooth tissue ( 31 P) and to identify diagenetic alterations ( 27 Al, 57 Fe, 88 Sr).…”
Section: Methodsmentioning
confidence: 99%
“…The limit of detection (LOD) was calculated as 3× standard deviation (SD) of this blank signal. Data reduction was performed with an in-house developed MS Excel Macro 90 . All blank corrected values smaller than the LOD were set to zero.…”
Section: Methodsmentioning
confidence: 99%
“…These data were exported from ArcGIS® and imported into Microso® Excel where the coordinates between the start and endpoint were calculated for each data point of the time resolved line scans. 25 The line scan data equipped with x-y coordinates were re-imported into ArcGIS® and displayed as a direct overlay of the otolith image. In consecutive steps outlier detection, 3-D visualisation and data integration were performed directly in ArcGIS®.…”
Section: Spatial Data Referencing and Statistical Analysismentioning
confidence: 99%
“…successfully been applied and published recently by ref. 25. In this work, the further development and application of imaging laser ablation split stream ICP-MS/MC ICP-MS is presented for the analysis of the elemental and Sr isotopic distributions in a sh otolith sample for the rst time.…”
Section: Introductionmentioning
confidence: 99%